The ownership of metal resources in religions law and legislation - عبد الحسين مضر (lark, 2020)
The research tackles the ownership of metal resources in religions law and legislation. Generally, metals are considered as one of the resources given by almighty allah in order to get benefit from them. They are not restricted for use by a specific generation; however, their benefit is for all people. Hence, the study is worth noting, because it conducts a comparative study in law. The research consists their section. The first section gives an insight about related term about the study. The second section discusses the ownership of metal resource in religious law. The third section argues the ownership legislation. finally; the research ends up with conclusion and reference.